THE REFORMS OF THE INHERITANCE LAW IN THE PROCESS OF CODIFICATION OF THE MACEDONIAN CIVIL LAW - Dejan Mickovik, Angel Ristov (Harmonius, 2016)
In Republic of Macedonia is ongoing the biggest reform in the legal system by preparing of the Civil code. Integrative part of the codification will be the Inheritance Law. Despite the dramatically changes and modern tendencies connected with inheritance, Macedonian inheritance law has not undergone significant changes for more than seven decades. In the article, authors are presenting the latest proposals contained in the Draft of Book 4 of the Civil code – Inheritance Relations, that were prepared as a result of the problems in the practice, upon the modern solutions from the comparative inheritance law. Among them, the most important will be the improvement of the inheritance law position of the spouse, by predicting the right on usufruct of the Family home in second inheritance rank. The authors believe that proposals for better protection of the creditors in the inheritance process will contribute to greater legal certainty. Predicting a special regime of inheritance for agricultural land and farms as well as for company shares and stakes will be also a significant reform, as well as the novelties in the conditions for realization of the forced share.
Keywords: Inheritance. - Inheritance Law. – Civil law codification. –Forced share